Stwardnienie rozsiane a zdolność do podjęcia istotnych obowiązków małżeńskich - Sztychmiler, Ryszard; Fryc, Jarosław Ch.; Drelich, Bożena (Ius Matrimoniale, 1997)
The results of clinical research indicates that multiple sclerosis is a neurological disease of the central nervous system. As a disease which directly affects brain cells, it may cause severe psychological and physiological dysfunctions in some of its victims. The principal psychological effects consist of cognitive and affective disturbances. Among cognitive deficites are memory loss and severe difficulty in conceptual reasoning. These deficits are likely to deprive the person affected by the disease of the ability to understand, reason, and elicit deliberate choice. Severe emotional disturbance indicative of a substantial change in personality. Such a change in personality may incapacitate multiple sclerosis victims in several aspects of their intrapsychic and interpersonal life. In marital relationship, a person may be rendered incapable of fulfilling the essential obligations of marriage. The physiological effects which have important juridic consequences are in the area of sexual dysfunctions. If these effects are present at the time of exchanging consent, a marriage court may have to look for possible functional impotence. If the dysfunction becomes evident after the marriage, the only approach seems to be to investigate the possibility of incapacity to assume the perpetuity of the right to sexual intercourse. If this approach is adopted, the basis for this incapacity is to be found in c. 1095, 3°, which requires that the cause of incapacity to assume the essential obligations of marriage be „psychic” in nature. The fact that someone has been diagnosed as having multiple sclerosis does not constitute definitive basis for the juridic conclusion that such a person is inept for or incapable of contracting marriage. The disease affects each person differently and, hence, interpatient variability with regard to physiological effects is inevitable. Therefore, all patients cannot be regarded as lacking in discretion of judgement and/or in their capacity to assume the essential obligations of marriage. Each case is unique and, therefore, each case must be investigated under an appropriate caput or capita nullitatis according to its particular circumstances.